Agregação de valor ao pescado: análise sensorial de pescados enlatados em salmoura e em forma de patê - Dentz, Bruna Alessandra Von (2022)
This study aimed to evaluate the quality presented by canned fish of four species of freshwater fish, tilapia (Oreochromis niloticus), tucunaré (Cichlao cellaris), piavuçu (Leporinus macrocephalus) and lambari (Astyanax altiparanae), being them in the form of product in brine and in the form of pâtés. There were eight treatments: TIL – Tilapia in Brine, TUC – Peacock Bass in Brine, LAM – Lambari in Brine, PIA – Piavuçu in Brine, TILP – Tilapia in Pâté, TUCP – Peacock Bass in Pâté, LAMP – Lambari in Pâté, and PIAP – Piavuçu a tie. Twenty-four cans of 270 grams of canned content were used and microbiological, physical-chemical and sensory analyzes were performed. Regarding the acceptance test of the products, it could be observed that there were differences in relation to the attributes appearance, aroma, flavor and overall impression. The results show that there was a great acceptance of canned foods from all treatments, and the degree of acceptance of pâtés was superior to all products in brine, with piavuçu pâté being the best of all. The analysis of purchase attitude and frequency of consumption of canned goods and the results showed that canned pâté showed higher acceptance rates in the global evaluation, with emphasis on piavuçu pâté, although the treatments in brine also had good rates of acceptance. It is concluded that the production of canned goods and their use in pâtés can add value to all the species studied, as well as enable the diversification of products derived from this raw material that is easy to prepare, without the need for refrigeration..